Characteristic Analysis of the Soil Bacterial Community Structure of Dendrocalamus brandisii from Seven Geographical Provenances in Yunnan Province - Qian Chen; Manyun Zhang; Negar Omidvar; Zhihong Xu; Shahla Hosseini Bai; Chaomao Hui; Weiyi Liu (Agronomy)
Soil is the basis of bamboo growth and quality formation of bamboo shoots and has an important contribution to the sustainable development of agriculture. To this end, We studied the soil properties and microbial communities of Dendrocalamus brandisii by collecting twenty-one soil samples from its seven typical geographic provenances in Yunnan Province, China. Bacterial 16S rRNA gene amplicons were used to detect soil bacteria and predict bacterial functions using Tax4Fun. The results indicated that the soil bacterial diversity indices (ACE, Chao1, Simpson, and Shannon) were significantly different among different geographical provenances. The dominant bacterial groups at the phylum level in all seven regions were Proteobacteria (19.78~29.06%), Actinobacteria (13.53~30.01%), Chloroflexi (8.03~31.47%), and Acidobacteria (7.12~19.17%), with markedly different constitution proportions. Total phosphorus, available potassium, and pH were the main environmental factors affecting soil bacterial communities. There were significant differences in the secondary metabolic pathways and phenotypes of soil bacterial functions, exhibiting a diversity of functions. The geographical variables of the soil bacterial community in D. brandisii varied with spatial scales. Environmental factors such as available potassium (AK), pH, and total nitrogen (TN) have an impact on soil bacterial communities.